2022
DOI: 10.1007/s11136-022-03150-x
|View full text |Cite
|
Sign up to set email alerts
|

“A fog that impacts everything”: a qualitative study of health-related quality of life in people living with HIV who have cognitive impairment

Abstract: Background Cognitive impairment (CI) in people living with HIV (PLWH) is an important health concern in the context of an ageing HIV population. Impacting 14–28% of PLWH, CI is associated with lower health-related quality of life (HRQoL), however, evaluation of the illness-specific factors comprising HRQoL in PLWH with CI have not been assessed. Objective We sought to contribute evidence toward an understanding of HRQoL and identify domains of HRQoL in PLW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…In this study, we examined a comprehensive set of HRQL scales, selected to represent the domains (physical function, cognition, social connectedness, physical and mental health and wellbeing, self-concept, HIV stigma, and acceptance of cognitive impairment and control over cognitive health outcomes) identified as comprising HRQL in PLWH with cognitive impairment. 19 The findings confirmed the relevance of the domains in a larger group of PLWH with cognitive symptoms as scores loaded primarily onto one common factor. This indicated that there is one underlying construct driving scores and that each domain fits onto this single theoretical construct, which we identified as HRQL based on previous qualitative work.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In this study, we examined a comprehensive set of HRQL scales, selected to represent the domains (physical function, cognition, social connectedness, physical and mental health and wellbeing, self-concept, HIV stigma, and acceptance of cognitive impairment and control over cognitive health outcomes) identified as comprising HRQL in PLWH with cognitive impairment. 19 The findings confirmed the relevance of the domains in a larger group of PLWH with cognitive symptoms as scores loaded primarily onto one common factor. This indicated that there is one underlying construct driving scores and that each domain fits onto this single theoretical construct, which we identified as HRQL based on previous qualitative work.…”
Section: Discussionsupporting
confidence: 64%
“…The instruments chosen to represent and ‘operationalise’ the HRQL domains identified 19 had to fulfil several criteria. This included: i) shown to have acceptable reliability and validity, preferably tested with HIV patients previously; ii) reasonably short in terms of time to complete; and iii) preferable provide (clinically) relevant cut-off points.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing symptoms is important as they can occur across multiple conditions and often involve similar biological mechanisms, enabling the use of similar treatment approaches. Brain fog, for example, has been studied in multiple conditions also involving neuroinflammation such as chemotherapy receivers, fibromyalgia, lupus, HIV, chronic fatigue syndrome, celiac disease, postural tachycardia syndrome, and thyroid disorders (Alford et al, 2022; Mackay, 2015; Ross et al, 2013; Samuels & Bernstein, 2022; Theoharides, Stewart, Hatziagelaki, & Kolaitis, 2015). Most recently, brain fog has been denoted as a major and long‐term symptom of SARS‐CoV‐2‐19 infection (Asadi‐Pooya et al, 2022; Callan et al, 2022) also attributed to neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%